2010
DOI: 10.1038/cgt.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of NF-κB decoy oligodeoxynucleotide suppresses pulmonary metastasis by murine osteosarcoma

Abstract: Nuclear factor-kappa B (NF-kB) has a pivotal role in the progression and distant metastasis of cancers, including malignant bone tumors. To inhibit NF-kB activation, a new molecular therapy using synthetic double-stranded oligodeoxynucleotide (ODN) as a 'decoy' cis element against NF-kB has been developed. To determine whether pulmonary metastasis of osteosarcoma is reduced by inhibiting the action of NF-kB, NF-kB decoy ODN was transfected into the nuclei of murine osteosarcoma cells with high pulmonary metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…NF-κB has also been reported to have a central and specific role in the regulation of metastasis in LM8 cells, because NF-κB decoy transfection inhibited pulmonary metastasis of these cells. 27 In the present study, phosphorylation levels of FAK at the cell protrusion region and NF-κB activity were suppressed in shPP2A cells, suggesting that PP2A Cα regulates cell migration and metastasis by controlling FAK and NF-κB activity.…”
Section: Discussionsupporting
confidence: 55%
“…NF-κB has also been reported to have a central and specific role in the regulation of metastasis in LM8 cells, because NF-κB decoy transfection inhibited pulmonary metastasis of these cells. 27 In the present study, phosphorylation levels of FAK at the cell protrusion region and NF-κB activity were suppressed in shPP2A cells, suggesting that PP2A Cα regulates cell migration and metastasis by controlling FAK and NF-κB activity.…”
Section: Discussionsupporting
confidence: 55%
“…We have also shown that continu- ously activated NF-κB is related to the high incidence of lung metastasis of LM8 cells (6)(7)(8). LUBAC-induced linear polyubiquitination plays crucial roles in NF-κB activation, and induced expression of LUBAC augments NF-κB activation (19)(20)(21).…”
Section: Discussionmentioning
confidence: 75%
“…We have previously observed that NF-κB is involved in the initial stage of lung metastasis of LM8 osteosarcoma cells (7) and that the induction of LUBAC components enhances NF-κB activation (20). Therefore, we evaluated the expression levels of the LUBAC subunits (HOIP, HOIL-1L, and SHARPIN) in Dunn and LM8 cells to investigate the potential involvement of LUBAC-mediated NF-κB activation in the lung metastasis of osteosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han [157]. DNA decoys are double stranded oligonucleotides recognized by DNA-binding proteins, hence trapping them and depleting their function [158][159][160]. Transfection of SATB1 decoy DNAs significantly reduced proliferative capacity of MDA-MB231 cells and drastically abolished their invasive and metastatic potential.…”
Section: Therapeutic Approach-satb1 As Molecu-lar Targetmentioning
confidence: 99%